Architectural and Heritage Experience Through Playful Learning (An Interdisciplinary and Exploratory Action Research Focused on The Egyptian Context) - Salama, Atheer Ahmed (AUC Knowledge Fountain, 2023)
“The lack of awareness of the value of heritage and the lack of opportunities to engage in preserving and safeguarding heritage in the public sphere not only puts the heritage in risk of being irremediably lost. It also impoverishes the younger generation’s sense of identity and belonging within its respective socio-cultural continuum, and thus limits its ability to engage and contribute meaningfully to society at large” (UNESCO, 2021). With conducting this research, the researcher believes that heritage-themed analog games may carve the younger generation’s memory of heritage, allowing them to boost their sense of identity and belonging; thus, widening their ability to engage and contribute meaningfully to society at large. There is a shortage in research and publications that analyze the role of analog games in heritage education and that document the process of design and implementation of heritage knowledge dissemination channels (programs, toolkits, and games). The researcher starts the exploration of this thesis with a belief in the potential of heritage-themed games in raising awareness of heritage and architecture, which could indirectly contribute to the fields of heritage conservation and management, and architecture in Egypt. The researcher explores the performance and effectiveness of heritage-themed analog games as knowledge dissemination tools of heritage and architecture for children in Egypt, especially for the age groups of 9-14 years old. The thesis exploration is guided by the following question: What are the effective components and aspects in games that could serve heritage and architecture knowledge dissemination and public awareness for children of age 9-14 years old in Egypt? One of the thesis outcomes is presenting a game proposal that manifests a developed design criteria for heritage analog games based on a thorough evaluation and analysis of both the design and the player experience of the studied games and activities. The research results include a set of guidelines for designing effective heritage-themed and architectural analog games that are knowledge-based for raising architectural and heritage awareness for the nine to fourteen years old age groups. As a main component of the research results, the researcher provides to the readers of all relevant disciplines a thorough documentation of the designed experiences of the research experiment, including the participants’ backgrounds and perceptions before, during, and after the experiment. The thesis as a whole is an exploratory-action research (Smith and Rebolledo, 2021). This research followed a qualitative research strategy with a Grounded Theory methodology and features of a naturalistic system of inquiry. The research submittals and results are based on a unique fieldwork of mixed methods of experimental and descriptive types of research work, and a participatory design approach with children of age group nine to fourteen years old. The submitted research results are only one stop in this journey, where the research findings and recommendations add value to both academia and practice for further research and design proposals. This research contribution extends beyond the borders of disciplines, as it presents valuable findings, analysis, and applicable proposals to the following fields: game design, ludology, education, architectural design, architecture pedagogy, heritage conservation, heritage management, architecture education, history education, heritage education, and possibly more fields that may find inspiration in the work done in this research journey. The interdisciplinary aspect of this research is a core factor in the whole process, starting with desk research that shaped a strong literature review, passing by several case studies and past research, which then aided the process of the research design and experimentation phases, to then reach the phase of documenting the findings and analyzing everything with regard to all the knowledge gained from the different disciplines, and ending the thesis with recommendations and proposals that giveback to those disciplines.